The well qualified teacher of bright children - Taylan, Marjorie P. 1941- (College of Education, University of the Philippines Diliman, 1967)
The aim of the study was to present the essential qualities of a well-qualified teacher of bright children. A library reference work was undertaken in gathering the data. The study maintained that well-qualified teachers of bright childen should be brighter than average teachers. They should be better prepared in the subject matter to be taught than what is necessary for average teachers. They should possess special tolerance and sympathy for the faults and annoying characteristics of the children and they should have undertaken special training.